DNA damage and proteomic profile changes in rat salivary glands after chronic exposure to inorganic mercury - Aragão, Walessa Alana Bragança (2022)
Mercury (Hg) is a toxic metal that became a public health problem due to environmental contamination caused by anthropogenic activity. In this sense, oral homeostasis can undergo changes due to the toxic effects of metal on the salivary glands. Therefore, our objective was to investigate the proteomic and genotoxic changes in salivary glands after exposure to inorganic mercury (IHg). Forty Wistar rats that were divided into a control group, which received distilled water, and an exposed group, which received 0.375 mg/kg of mercury chloride for 45 days via orogastric gavage. After that, the animals were euthanized, and the parotid and submandibular glands were collected for analysis of the genotoxic effects, using the comet assay and proteome global profile assessment. The results showed that IHg promoted damage to cellular DNA associated with proteomic changes that showed events such as oxidative stress, mitochondrial dysfunction, changes in the cytoskeleton, and apoptosis. Therefore, these findings show a profile of molecular changes due to the interactions of IHg with several proteins and mechanisms inherent to the cell, which consequently may result in dysfunction of the salivary glands and impaired homeostasis of the oral cavity.